Pre-biologic assessment of adherence in severe asthma and association with biologic continuation: a UK Severe Asthma Registry Study - Ronald McDowell; Sherif Gonem; Chloe I Bloom; Ian Pavord; Salman Siddiqui; John Busby; Rekha Chaudhuri; Adel H Mansur; Liam G Heaney; Robert Stone; Thomas Brown; Anna Claire Murphy; et al. (BMJ Open Respiratory Research, 2025)
Background Biologic therapies are approved for uncontrolled severe asthma despite good adherence to inhaled corticosteroids (ICS) and additional controllers. We examined the adherence assessments used across UK Severe Asthma Centres (SACs) and their relationship with biologic continuation and response.Methods UK SACs completed a quantitative survey on adherence assessment practices in 2022. We included all adult patients with severe asthma patients on ICS starting biologic therapy from the UK Severe Asthma Registry, which collects pre-biologic adherence data, including medication possession ratio (MPR), fractional exhaled nitric oxide (FeNO) suppression testing and serum prednisolone levels. Biologic continuation and response were defined as continuation on any biologic and the same biologic after 1 year, respectively. Associations were determined using multivariable logistic regression.Results At 21 SACs, MPR for ICS was assessed at 19 (90%) centres, prednisolone and/or cortisol levels in patients on daily oral corticosteroids at 15 (71%), and FeNO suppression testing at 9 (43%). Of 3307 biologic-initiated patients, 1943 (59%) had MPR for ICS recorded, of which 1802 (93%) demonstrated good adherence (≥75% MPR). Only 110 (9%) and 272 (16%) had FeNO suppression and serum prednisolone results, respectively. Good ICS adherence was associated with 2.65-fold higher odds (95% CI 1.02 to 6.91) of biologic continuation, but not with biologic response (OR 1.37, 95% CI 0.50 to 3.76).Conclusion Good pre-biologic ICS adherence, measured using MPR, is associated with biologic continuation at 1 year. Further research is needed to determine whether baseline adherence predicts biologic response based on clinical and biologic criteria.